Edukasi Keamanan Akun Digital melalui Media Infografis Pencegahan Phishing dan Perlindungan Kode OTP pada Siswa SMA Amanatul Ummah Surabaya - Arinda Tri Apriliyah; Dina Anggraeni Susesti; Mohammad Ghofirin; Dwi Novitasari (Kilau Publishing, 2026)
This community service activity aimed to provide digital account security education through infographics on phishing prevention and One-Time Password (OTP) protection for students at SMA Amanatul Ummah Surabaya. The activity involved 40 students and was conducted through interactive explanations, discussions, question-and-answer sessions, and case analysis. The evaluation used a Likert-scale response questionnaire to assess the clarity, attractiveness, usefulness, and ease of understanding of the media. The results showed an average percentage of 85.4%, categorized as very good. The infographic received positive responses as an engaging, concise, and easy-to-understand medium for digital account security education.